Keterbatasan Sistem Pengelolaan dalam Mendukung Pemasaran Digital pada Pendidikan Kejuruan Berbasis Pesantren - Fatimatul Husna; Mohammad Syifaur Rizal (CV. Laskar Karya, 2026)
The rapid development of digital technology has encouraged educational institutions to adopt digital marketing as a strategic instrument to enhance competitiveness. However, in vocational education based on Islamic boarding schools, the implementation of digital marketing has not been fully supported by adequate management systems and human resource capacity. This study aims to analyze the limitations of management systems in supporting digital marketing and to identify institutional-based optimization efforts. This research employs a qualitative approach with a case study method at SMK Nurul Jadid. The research subjects include the principal, teachers, and staff involved in digital marketing activities. Data were collected through interviews, observations, and documentation, while data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that digital marketing activities have been implemented but are not yet systematically managed, human resource capacity remains limited, and institutional strengthening is required to optimize management practices. The novelty of this study lies in its emphasis on institutional aspects of digital marketing management within the context of Islamic boarding school-based education. The implications highlight the importance of system integration, human resource development, and policy support in achieving effective and sustainable digital marketing management.